JUDICIAL PROTECTION OF REAL PROPERTY RIGHTS - Tasić, Anđelija; Lazić, Miroslav (COLLECTION OF PAPERS, FACULTY OF LAW NIŠ, 2024)
Classical institutes, such as property law protection, have withstood the test of time from Roman law to the present day. The paper presents five lawsuits aimed at judicial protection of property rights - actio rei vindication, actio publiciana, actio negatoria, actio confessoria actio and pignoris. In the paper, the authors tried to point out the (non)existence of the legal significance of the traditional division of property lawsuits. Furthermore, they pointed out the reasons for providing legal protection. Regarding the procedure, they emphasized the lawsuit for the return of things, which is most fully regulated according to the ZOSPO. The authors noted that, although this institute survived in its essence, some new tendencies, such as the right to a home, established by the practice of the European Court of Human Rights, and confirmed by the decisions of the Constitutional Court of the Republic of Serbia, call into question, if not the very concept of property rights, the they restrictions on the use of their own belongings.